2019
DOI: 10.1111/jce.13927
|View full text |Cite
|
Sign up to set email alerts
|

The fourth cryoballoon generation with a shorter tip to facilitate real‐time pulmonary vein potential recording: Feasibility and safety results

Abstract: Introduction: Time-to-isolation (TTI) guided ablation protocols have been developed to ensure durable pulmonary vein isolation (PVI) in cryoballoon ablation (CBA). The aim was to determine the feasibility and safety of the fourth generation cryoballoon (CBG4) with a shortened tip. Methods and Results:Consecutive patients scheduled for initial atrial fibrillation (AF) ablation were prospectively included. PVI with the 28 mm CBG4 and the latest 20 mm spiral-mapping catheter (SMC) was performed.A total of 302 pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 18 publications
5
34
1
Order By: Relevance
“…As confirmed by our results, late isolation (eg, later than 60 seconds) in the context of single freeze is associated with a significant rate of late PVr (50% vs 22.6%; P < .001) in line with previous observations . Technological innovation in recording catheters lead to higher rates of RT; however, encouraging success rates were reported even in CbA performed without a recording catheter . Despite the relatively low rate of RT in our population of redo procedures, we confirmed, overall, a comparable behavior of predictors in both groups of PVs (with and without available RT recordings).…”
Section: Discussionsupporting
confidence: 91%
“…As confirmed by our results, late isolation (eg, later than 60 seconds) in the context of single freeze is associated with a significant rate of late PVr (50% vs 22.6%; P < .001) in line with previous observations . Technological innovation in recording catheters lead to higher rates of RT; however, encouraging success rates were reported even in CbA performed without a recording catheter . Despite the relatively low rate of RT in our population of redo procedures, we confirmed, overall, a comparable behavior of predictors in both groups of PVs (with and without available RT recordings).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is interesting to see whether the incidence of ATs that are either PV‐dependent or originate from the antral index ablation line can be prevented by optimizing the index procedure. To improve on these shortcomings, additional tools such as the ablation index for RFC ablation (which was only partially included in this study) or the release of the fourth‐generation CB are now implemented in clinical practice 25,26 . It has already been reported that a minimum ablation index is associated with PV reconnection 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The CB4 with a shorter distal tip is safe and effective, and allows determination of TTI in 78-85% of PV. [44][45][46] Several randomized clinical trials have been carried out to investigate the efficacy and long-term outcomes of CB ablation (Table), which were almost identical to those of RFCA. 8,47-51 Furthermore, CB-based PV isolation seems to be less operator dependent and more reproducible than RF-based PV isolation in the setting of paroxysmal AF ablation, 52 although various parts of the procedure, such as the freezing protocol, were not standardized.…”
Section: Cb Ablation: Precautionsmentioning
confidence: 99%
“…66 CB4 could record real-time online PV potential with a low incidence of CB dislodgment. [44][45][46] Further research into tailored CB ablation protocols using CB4 to reduce unnecessary cryoenergy applications is required.…”
Section: Minimally Invasive and Tailored Cb Ablationmentioning
confidence: 99%